Surveillance of bluetongue virus antibody in goats using a recombinant VP7-based indirect ELISA in the coastal saline area of West Bengal, India - Raj K. Singh; Karam Chand; Sanchay K. Biswas; Subhasis Batabyal; Anakn De; Bimalendu Mondal (Veterinaria Italiana, 2009)
The authors describe the serological surveillance of bluetongue virus (BTV) group-specific antibody in goats of the coastal saline (Sunderban) area of West Bengal, India. A recombinant viral protein 7 (rVP7)-based indirect enzyme-linked immunosorbent assay (ELISA) was used to detect the antibody in sera. The bacterially expressed rVP7 was purified by affinity chromatography. The diagnostic performance of the assay was assessed by comparing it to the commercially available previously validated competitive ELISA. Using the control and 1 202 test sera, the cut-off value, sensitivity and specificity as well as other performance characteristics e.g. the Youden index, efficiency, positive and negative predictive value and prevalence were estimated. Field-collected goat sera (n = 1 202) were tested and a serological prevalence rate of 47% was observed in the study area.